Hubungan Tingkat Pengetahuan dan Perilaku Mencuci Tangan terhadap Kejadian Diare pada Siswa Sekolah Dasar - Karmayani, Ni Putu Ika; Diwyami, Ni Putu; Widyandari, Ni Made Ayu Sukma (STIKes Hamzar, 2025)
Diarrhea is an infectious disease in the gastrointestinal tract as a result of poor environmental sanitation and personal hygiene so that it can attack and kill all ages, but cases of diarrhea in children and infants can be at risk of causing death. Research purposes to analyze the relationship between the Level of Knowledge and Handwashing Behavior to the incidence of diarrhea in elementary students in the Puskesmas I area of West Denpasar. This research design uses quantitative descriptive with a cross-sectional approach. The total sample was 101 respondents using random sampling techniques. The data collection tool used was a questionnaire sheet. This research uses the Chi-Square test. Research Results: The Hand Washing Behavior variable has a significant relationship with the incidence of diarrhea because the results of the P-value show results <0.05, and have a 3.075 greater influence on the incidence of diarrhea. The conclusion from this research is The Hand Washing Behavior variable has a significant relationship with the incidence of diarrhea because the results of the P-value show results <0.05, and have a 3.075 greater influence on the incidence of diarrhea.